UPAYA PENINGKATAN KEMAMAPUAN PEMECAHAN MASALAH MATEMATIKA SISWA DI SEKOLAH MENENGAH PERTAMA MELALUI PENDEKATAN PEMBELAJARAN MATEMATIKA REALISTIK - Sri Indah Lestary; Marzuki Ahmad; Roslian Lubis (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2020)
This study aims to improve students’ mathematical problem solving ability through realistic mathematic learning approach on the topic of the theorem of Phytagoras at the eighth grade students. The research was conducted by applying Class Action Research (CAR) with 25 students as the subject. Instrument of the research was test and observation. The research consists of two cycles. The first cycle showed (a) the test showed the students’ achievement of the theorem of Phytagoras was 47.02 (enough category) and (b) the questionnaire showed the average of students’ activities was 89.29 (high category). Furthermore, the second cycle showed (a) the test showed the students’ achievement of the theorem of Phytagoras 85.48 (very good category) and (b) the questionnaire showed the average of students’ activities was 96.42 (very high category). It’s concluded realistic mathematic learning approach was able to improve students’ mathematic mathematical problem solving ability through realistic mathematic learning approach on the topic of the theorem of Phytagoras at the eighth grade students.